Tasa de interés y morosidad en las instituciones microfinancieras peruanas, periodo 2015-2020 - Obeso Galarreta, Hisenia Raquel (2021)
The present study proposes as a research objective to determine the influence of the active interest rate on the delinquency of Peruvian microfinance institutions, period 2015-2020, for which a non-experimental - correlational study was proposed that, within its mixed approach, compiled statistical material from the publications of the Superintendency of Banking and Insurance of Peru. Likewise, the object of study was the Peruvian microfinance institutions. When evaluating the variables active interest rate and delinquency, the correlation between the analysis variables was positive, since the Spearman correlation coefficient is 0.3351. Finally, by estimating the validated panel generalized least squares (GLS) model of first-order autocorrelation and heteroscedasticity, it was determined that the lending rate has a positive and significant influence on the delinquency of microfinance institutions, therefore can conclude that the active interest rate of loans to microenterprises increases by one percentage point, then the delinquency of loans to microenterprises increases by 0.1931 percentage points, thus confirming the theory of Stiglitz and Weiss affirm that as interest rates increase, eventually borrowers with safer projects will leave the market, leaving only borrowers with risky projects.